Temporal trends in patients with peripheral artery disease influenced by COVID-19 pandemic - Keller, Karsten; Schmitt, Volker H.; Hobohm, Lukas Martin Alois; Brochhausen, Christoph; Münzel, Thomas; Espinola-Klein, Christine (Journal of Clinical Medicine, 2022)
Background: The COVID-19 pandemic influences the health care management of acute and chronic diseases. Data concerning the influence of the pandemic on hospitalizations of patients with peripheral artery disease (PAD) are sparse. Methods: We analysed all patients hospitalized due to PAD between 1 January 2019 and 31 December 2020 in Germany. Hospitalizations of PAD patients during the pre-pandemic year 2019 were compared to the pandemic year 2020. Results: Overall, 361,029 hospitalizations of PAD patients in the years 2019 and 2020 (55.4% aged ≥70 years; 36.6% females) were included in this study. In the pre-pandemic year of 2019, a total of 25,501 (13.2%) more hospitalizations due to PAD were detected compared to the COVID-19 pandemic year of 2020 (2019: 192,765 [53.4%] vs. 2020: 168,264 [46.6%], p = 0.065). Overall, in 610 (0.4%) of the hospitalization cases, a COVID-19 infection was diagnosed. Regarding interventional/surgical treatments, total numbers of peripheral endovascular intervention of the lower extremity decreased by 9.9% (83,845 vs. 75,519, p < 0.001), surgical peripheral artery revascularization of the lower extremity by 11.4% (32,447 vs. 28,754, p = 0.041) and amputations by 4.0% (20,612 vs. 19,784, p < 0.001) in 2020 compared to 2019. The case fatality rate (2.6% vs. 2.4%, p < 0.001), as well as MACCE rate (3.4% vs. 3.2%, p < 0.001), were slightly higher during the pandemic year 2020 compared to the pre-pandemic year 2019. Conclusions: The COVID-19 pandemic influenced the number of hospitalizations of PAD patients with a 13.2% reduction in hospital admissions and decreased total numbers of revascularization and amputation treatments.
Gesehen am 20.01.2023